2014
DOI: 10.1111/liv.12482
|View full text |Cite
|
Sign up to set email alerts
|

Occult HBV infection in Morocco: from chronic hepatitis to hepatocellular carcinoma

Abstract: This study helps to understand the current status of OBI and its impact on the severity of liver disease in Moroccan patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…OBI may be observed in the window period of acute HBV infection [16] in blood donors and in recipients of blood and blood products [9,17,18] , in patients with HCV chronic infection [7,19] , in cryptogenic chronic hepatitis, in patients under pharmacological suppression of the immune system [20,21] and in those with immunodepression due to HIV infection; it has also been associated to the development of hepatocellular carcinoma [22][23][24][25][26][27][28][29][30] . It has been shown that the hepatitis B virus maintains its pro-oncogenic properties in OBI [31] and that its presence in patients with chronic hepatitis C is associated with a higher risk of disease progression and HCC development [32][33][34][35][36] and with a reduced response to alfa interferon treatment [37][38][39] . The clinical importance of OBI is also underscored by the need for nucleot(s)ide treatment to prevent the recurrence of HBV infection in HBsAgnegative/anti-HBc-positive patients in various immunosuppressive settings [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…OBI may be observed in the window period of acute HBV infection [16] in blood donors and in recipients of blood and blood products [9,17,18] , in patients with HCV chronic infection [7,19] , in cryptogenic chronic hepatitis, in patients under pharmacological suppression of the immune system [20,21] and in those with immunodepression due to HIV infection; it has also been associated to the development of hepatocellular carcinoma [22][23][24][25][26][27][28][29][30] . It has been shown that the hepatitis B virus maintains its pro-oncogenic properties in OBI [31] and that its presence in patients with chronic hepatitis C is associated with a higher risk of disease progression and HCC development [32][33][34][35][36] and with a reduced response to alfa interferon treatment [37][38][39] . The clinical importance of OBI is also underscored by the need for nucleot(s)ide treatment to prevent the recurrence of HBV infection in HBsAgnegative/anti-HBc-positive patients in various immunosuppressive settings [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the results of several studies indicate that OBI exists in patients with hepatitis, cirrhosis, or liver cancer [Chan et al, 2002;Simonetti et al, 2010;Huang and Hollinger, 2014;Kitab et al, 2014]. However, cross-sectional analysis revealed that only a small number of people have abnormal liver function, while our results indicate that alanine transaminase, total bilirubin, and other liver function test results were similar between OBI and non-HBV infected patients.…”
Section: Paient Genotypementioning
confidence: 45%
“…Occult hepatitis B virus infection (OBI) can be defined as the presence of hepatitis B virus (HBV) DNA in the blood or liver, in the absence of detectable serum hepatitis B surface antigen (HBsAg), and with or without detectable antibodies to the hepatitis B core protein (anti-HBc) [Brechot et al, 2001;Raimondo et al, 2008]. Although the mechanism and clinical implications of OBI have not been clearly elucidated, OBI has been associated with the risk to develop cirrhosis and hepatocellular carcinoma [Chan et al, 2002;Simonetti et al, 2010;Huang and Hollinger, 2014;Kitab et al, 2014]. In addition, immunosuppression in patients with OBI may lead to HBV reactivation [Knoll et al, 2005;Macera et al, 2014;Seetharam et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The OBI prevalence in chronic HCV patients was 45.7% (42/92) in Morocco[25] and 20% (18/50) in Iran[26], while none of 100 Portuguese patients showed serum OBI[19]. A retrospective study in Taiwan showed that serum OBI prevalence as determined by nested PCR using 3 sets of primers in patients with chronic HCV infection was 14.8% (31 of 210), which did not differ from that of healthy controls (15%, 15/100), and the prevalence of OBI did not parallel the severity of liver disease (14.5% in chronic hepatitis, 8% in liver cirrhosis, and 22% in HCC)[27].…”
Section: Discussionmentioning
confidence: 99%